2005
DOI: 10.1038/sj.emboj.7600790
|View full text |Cite
|
Sign up to set email alerts
|

Kar3 interaction with Cik1 alters motor structure and function

Abstract: Kar3, a kinesin-14 motor of Saccharomyces cerevisiae required for mitosis and karyogamy, reportedly interacts with Cik1, a nonmotor protein, via its central, predicted coiled coil. Despite this, neither Kar3 nor Cik1 homodimers have been observed in vivo. Here we show that Kar3 is a dimer in vitro by analytical ultracentrifugation. The motor domains appear as paired particles by rotary-shadow electron microscopy (EM) and circular dichroism (CD) spectroscopy of the nonmotor region shows characteristics of helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
1
33
2
Order By: Relevance
“…studies suggest that members of the Kinesin-14 family actually possess the ability to destabilize rather than to stabilize MTs (Endow et al, 1994b;Chu et al, 2005;Sproul et al, 2005). Our data showed that in human cells and in Xenopus extracts Kinesin-14 proteins promote the outward movement of the spindle poles and increase half spindle length in monopolar spindles (data not shown).…”
Section: Kinesin-14s Affect Spindle Length Through Mt Slidingmentioning
confidence: 48%
“…studies suggest that members of the Kinesin-14 family actually possess the ability to destabilize rather than to stabilize MTs (Endow et al, 1994b;Chu et al, 2005;Sproul et al, 2005). Our data showed that in human cells and in Xenopus extracts Kinesin-14 proteins promote the outward movement of the spindle poles and increase half spindle length in monopolar spindles (data not shown).…”
Section: Kinesin-14s Affect Spindle Length Through Mt Slidingmentioning
confidence: 48%
“…However, diverse cellular processes such as transcription, mRNA processing, spindle dynamics, and sister chromatid cohesion were also represented within the intersection dataset. Interestingly, tolerance to HU requires KAR3 and CIK1, which encode proteins that physically interact to form a minus-enddirected kinesin (Chu et al, 2005;Sproul et al, 2005), consistent with recent studies that implicate Mec1 and Rad53 in the regulation of spindle dynamics (Krishnan et al, 2004;Bachant et al, 2005). These genome-wide screens reveal that resistance to replication stress engages diverse cell regulatory processes.…”
Section: B=63mentioning
confidence: 48%
“…complex [29][30][31][32][33][34][35] . Indeed, disruption of kinesin-14 alone or in combination with Lrs4 deletion, decreased subtelomeric DSB survival to levels similar to those seen in cells deficient in cohibin or Nup84 (Fig.…”
Section: Resultsmentioning
confidence: 99%